2016
DOI: 10.1039/c5cp06615h
|View full text |Cite
|
Sign up to set email alerts
|

Distinct structural and dynamical difference between supercooled and normal liquids of hydrogen molecules

Abstract: Supercooled hydrogen liquid as well as superfluid have continued to elude experimental observation due to rapid crystallization. We computationally realized and investigated supercooled hydrogen liquid by a recently developed non-empirical real-time molecular dynamics method, which describes non-spherical hydrogen molecules with the nuclear quantum effects. We demonstrated that the hydrogen supercooled liquid is not a simply cooled liquid but rather exhibits intrinsic structural and dynamical characters includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 37 publications
0
60
0
Order By: Relevance
“…We now calculate H, x, and ∆x for the more challenging case of an asymmetric double well potential, defined in one-dimensional, non mass-weighted space as Panels AI and BI of Figure 4 show x and ∆x, respectively, with the accompanying residuals in panels AII and BII, defined using Eq. (52). Despite the greater anharmonicity, both the Gaussian averages and the temperature transitioned averages are close to the exact quantum values for x and ∆x, with errors of 1% or less.…”
Section: B Double Well Potentialmentioning
confidence: 63%
See 1 more Smart Citation
“…We now calculate H, x, and ∆x for the more challenging case of an asymmetric double well potential, defined in one-dimensional, non mass-weighted space as Panels AI and BI of Figure 4 show x and ∆x, respectively, with the accompanying residuals in panels AII and BII, defined using Eq. (52). Despite the greater anharmonicity, both the Gaussian averages and the temperature transitioned averages are close to the exact quantum values for x and ∆x, with errors of 1% or less.…”
Section: B Double Well Potentialmentioning
confidence: 63%
“…We intend to explore the use of thermostatted trajectories for the calculation of correlation functions in future work, which will generalise the existing microcanonical approaches [49][50][51][52][53] to finite temperature. This article is concerned with improving the accuracy of the approximate canonical phase-space density and canonical statistical averages.…”
Section: Introductionmentioning
confidence: 99%
“…Another related issue would be inclusion of nuclear motion. In the present framework, an approximate treatment with nuclear wave packets would be possible [36][37][38][39]. These are open for future examinations.…”
Section: Discussionmentioning
confidence: 93%
“…In previous publications [32,33], we demonstrated that a model of floating and breathing localized electron wave * E-mail: ando_k@lab.twcu.ac.jp packets (EWP) with non-orthogonal valence-bond (VB) spincoupling [34][35][36][37][38][39][40] can be used to construct potential energy surfaces for single electron motion (ePES) as functions of the EWP positions. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain an alternative perspective, we have been studying a model of localized electron wave packets (EWPs) with non-orthogonal valence-bond (VB) spin-coupling [31][32][33][34]. It was originally developed for a polarizable and reactive forcefield model in condensed phase simulations to be combined with nuclear wave packets for light atoms [35][36][37][38]. For small molecules such as H 2 , LiH, BeH 2 , CH 2 , H 2 O, and NH 3 in * E-mail: ando k@lab.twcu.ac.jp the ground electronic state, the model gives reasonably accurate potential energy surfaces with the minimal number of EWPs [32].…”
Section: Introductionmentioning
confidence: 99%